Eksistensi Kesenian Wayang Kulit dalam Menjaga Kerukunan di Desa Sumber Arum Kabupaten Seluma - Ismail, Ismail; Sepri Yunarman; Nurhidayati, Sri Wahyu (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Traditional arts such as shadow puppets are a national cultural heritage that has high philosophical value and plays an important role in maintaining social harmony amidst the diversity of society. This study aims to explore how the existence of shadow puppetry contributes to maintaining social harmony in Sumber Arum Village, Seluma Regency. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, in-depth interviews, and documentation of traditional leaders, puppeteers, village heads, and local artists. The results show that shadow puppetry has been an important part of community life since 1976, brought by transmigrants from Yogyakarta. Shadow puppet performances are routinely held through activities such as Sedekah Bumi and supported by the establishment of the